Inheritance and maintenance of small RNA‐mediated epigenetic effects. (25th March 2022) - Quarato, Piergiuseppe; Singh, Meetali; Bourdon, Loan; Cecere, Germano
Abstract: Heritable traits are predominantly encoded within genomic DNA, but it is now appreciated that epigenetic information is also inherited through DNA methylation, histone modifications, and small RNAs. Several examples of transgenerational epigenetic inheritance of traits have been documented in plants and animals. These include even the inheritance of traits acquired through the soma during the life of an organism, implicating the transfer of epigenetic information via the germline to the next generation. Small RNAs appear to play a significant role in carrying epigenetic information across generations. This review focuses on how epigenetic information in the form of small RNAs is transmitted from the germline to the embryos through the gametes. We also consider how inherited epigenetic information is maintained across generations in a small RNA‐dependent and independent manner. Finally, we discuss how epigenetic traits acquired from the soma can be inherited through small RNAs. Abstract : Over the years, many studies have demonstrated the inheritance of acquired traits. Small RNAs are one of the molecules proposed to transmit such traits across generations. This review focuses on recent advances in the understanding mechanism of transmission of small RNAs to embryos and their maintenance in subsequent generations.